2017
DOI: 10.1111/joa.12762
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical map of the cranial vasculature and sensory ganglia

Abstract: There is growing evidence of a direct influence of vasculature on the development of neurons in the brain. The development of the cranial vasculature has been well described in zebrafish but its anatomical relationship with the adjacent developing sensory ganglia has not been addressed. Here, by 3D imaging of fluorescently labelled blood vessels and sensory ganglia, we describe for the first time the spatial organization of the cranial vasculature in relation to the cranial ganglia during zebrafish development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Additionally, studies in murine non-cerebral ECs showed that motor-neurons impact vascular patterning in the spinal cord [ 329 ], while blood vessels are important regulators of neural stem cell properties [ 330 ]. Zebrafish studies of cerebral neurovascular congruency suggest the vasculature is required for hindbrain development [ 331 ] and ganglia projections [ 332 ]. Conversely ablation of oxytocin in the hypothalamo-neurohypophyseal system results in defects of vascular patterning [ 333 ] and motor neurons were shown to be essential for vascular pathfinding in non-cerebral vessels [ 334 ].…”
Section: Non-endothelial Cells Required For Cerebrovascular Developmentmentioning
confidence: 99%
“…Additionally, studies in murine non-cerebral ECs showed that motor-neurons impact vascular patterning in the spinal cord [ 329 ], while blood vessels are important regulators of neural stem cell properties [ 330 ]. Zebrafish studies of cerebral neurovascular congruency suggest the vasculature is required for hindbrain development [ 331 ] and ganglia projections [ 332 ]. Conversely ablation of oxytocin in the hypothalamo-neurohypophyseal system results in defects of vascular patterning [ 333 ] and motor neurons were shown to be essential for vascular pathfinding in non-cerebral vessels [ 334 ].…”
Section: Non-endothelial Cells Required For Cerebrovascular Developmentmentioning
confidence: 99%
“…Afterward, they differentiate into Islet2 + neurons (orange) (Figure 1A). The developing zebrafish SAG lies between three main vessels, the primordial hindbrain channel (PHBC) that runs between the hindbrain and the otic vesicle (OV), the lateral dorsal aorta (LDA) beneath the OV ,and the primary head sinus (PHS) surrounding laterally the OV (Taberner et al, 2018;Figure 1B).…”
Section: Vasculature Regulates the Number Of Sag Neuroblasts By Restraining Cell Cycle Entry Of Neuroblastsmentioning
confidence: 99%
“…Cranial ganglia in vertebrates lie in close proximity to head blood vessels (Taberner et al, 2018), suggesting that vasculature might be an essential component of their niche. Notwithstanding, this question and the mechanisms involved in their communication remain to be addressed in the sensory PNS.…”
Section: Introductionmentioning
confidence: 99%
“…We focused on neurovascular interactions in the statoacoustic ganglion (SAG), which forms the sensory neurons that innervate mechanosensory hair cells of the inner ear and the brainstem. The developing zebrafish SAG lies between three main vessels, the Primordial Hindbrain Channel (PHBC) that runs between the hindbrain and the otic vesicle (OV), the Lateral Dorsal Aorta (LDA) beneath the OV and the Primary Head Sinus (PHS) surrounding laterally the OV 28 (Fig. 1b).…”
Section: Vasculature Regulates the Number Of Sag Neuroblasts Through mentioning
confidence: 99%
“…Some of the autocrine signals regulating the balance between sensory neuroblast proliferation and differentiation have been described [22][23][24][25][26][27] . Since cranial blood vessels lie in close proximity to forming cranial ganglia it seems likely that vascular signals also influence their development 28 . However, this question has yet not been addressed.…”
Section: Introductionmentioning
confidence: 99%